Antioxidant, analgesic and toxic potentiality of stephania japonica (Thunb.) miers. leaf - Rahman, Md Habibur; Alam, Md. Badrul; Chowdhury, N.S.; Kumar Jha, Mithilesh; M, Hasan; Khan, Md. Maruf; Rahman, Md. Saifur; Haque, M. Ekramul (© 2011 Asian Network for Scientific Information., 2016)
This article was published in International Journal of Pharmacology [© 2011 Asian Network for Scientific Information] and the definite version is available at: http://docsdrive.com/pdfs/ansinet/ijp/0000/25025-25025.pdf